Editorial: Jordan's Principle PSA in American Sign Language

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
Jordan’s Principle is a legal rule named in memory of a very special little boy named Jordan River Anderson. Jordan’s Principle makes sure that all First Nations children get the services they need when they need them. This applies to all services: including heath care, education, child welfare, and more. If your child, or someone you know needs services, call 1-855-JP-CHILD (1-855-572-4453) / 1-833-PJ-ENFAN (1-833-753-6326) or visit www.canada.ca/jordans-principle.